Contribution of Creative Entrepreneurs in Supporting Village Development Strategies Based on The Potential of Local Products - Nawangsih Nawangsih (Jurnal Ilmu Manajemen Advantage, 2021)
developing tourist villages and to identify the potential of local products as opportunities for creative economy. The type of research conducted is qualitative by using a case study approach. The research location was in the Semeru Bamboo Belt Workshop in Sumbermujur Village, Candipuro District, Lumajang Regency. The research informants consisted of: Semeru Belt Workshop Management, Business Actors, Consumers and the Community. The results of research conducted indicate that the contribution of creative entrepreneurs in supporting the development of tourism villages with products that they have is quite large, given the creative industry products produced are obtained by utilizing the considerable natural resource potential, namely handicraft products made from bamboo, which are in the region, although the types of products produced are still limited, due to the limited knowledge and skills possessed by these business actors. The potential of local products developed in Sumbermujur village is quite diverse. This is very useful in supporting tourism activities carried out, among others: excellence of agricultural products, which are processed into various kinds of culinary specialties with superior recipe bamboo shoots, bamboo batik crafts, and currently the ones that superior is bamboo crafts.